2019
DOI: 10.1093/mnras/stz1554
|View full text |Cite
|
Sign up to set email alerts
|

Origin of α-rich young stars: clues from C, N, and O

Abstract: A small set of chemically old stars that appear young by their independently derived masses has been detected. These are so-called α-rich young stars. For a sample of 51 red-giant stars, for which spectra are available from SDSS/APOGEE and masses are available from asteroseismic measures based on Kepler lightcurves, we derive the C, N and O abundances through an independent analysis. These stars span a wide range of N/C surface number density ratios. We interpret the high-mass stars with low N/C as being produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…However, a detailed binary evolution modelling of the non-degenerate channel is needed to make any conclusive predictions. It may also be possible that the second-branch objects are members of a peculiar Galactic subpopulation with a metallicity of about [Fe/H] ≈ −1 and a broad range of ages between 5 and 10 Gyr not included in the Besanćon model, for example Chiappini et al (2015), Martig et al (2015) and Hekker & Johnson (2019). However, it seems unlikely that a separate unidentified population comparable in size to that of the thin disc would be present in the solar neighbourhood.…”
Section: Constraining Stellar Evolution With Sdb Binariesmentioning
confidence: 99%
“…However, a detailed binary evolution modelling of the non-degenerate channel is needed to make any conclusive predictions. It may also be possible that the second-branch objects are members of a peculiar Galactic subpopulation with a metallicity of about [Fe/H] ≈ −1 and a broad range of ages between 5 and 10 Gyr not included in the Besanćon model, for example Chiappini et al (2015), Martig et al (2015) and Hekker & Johnson (2019). However, it seems unlikely that a separate unidentified population comparable in size to that of the thin disc would be present in the solar neighbourhood.…”
Section: Constraining Stellar Evolution With Sdb Binariesmentioning
confidence: 99%
“…There is also likely evidence of such products among field stars that are enriched in α elements, hence supposedly belonging to an old population [50,98,107,108,134,219].…”
Section: Occurrence Of Mergers / Products Of Binary Evolutionmentioning
confidence: 99%
“…The origins of young, high-α stars are still debated: Chiappini et al (2015) postulated that these stars could arise from inert gas near the ends of the Galactic bar; other authors note that they are frequently found in binary systems (Jofré et al 2016) and show evidence of mass transfer (Yong et al 2016; see also Hekker & Johnson 2019) which suggests that these stars are truly Blue Straggler stars (Matsuno et al 2018;Sun et al 2020). This could lead to an observationally young population of stars which is kinematically old and similar in chemistry to the older thick disk.…”
Section: Evolution Of the Metallicity Gradient In The Thick Diskmentioning
confidence: 99%